21st Century Sea‐Level Rise in Line with the Paris Accord. Issue 2 (9th February 2018) - Jackson, Luke P.; Grinsted, Aslak; Jevrejeva, Svetlana
Abstract : Abstract: As global average sea‐level rises in the early part of this century there is great interest in how much global and local sea level will change in the forthcoming decades. The Paris Climate Agreement's proposed temperature thresholds of 1.5°C and 2°C have directed the research community to ask what differences occur in the climate system for these two states. We have developed a novel approach to combine climate model outputs that follow specific temperature pathways to make probabilistic projections of sea‐level in a 1.5°C and 2°C world. We find median global sea‐level (GSL) projections for 1.5°C and 2°C temperature pathways of 44 and 50 cm, respectively. The 90% uncertainty ranges (5%–95%) are both around 48 cm by 2100. In addition, we take an alternative approach to estimate the contribution from ice sheets by using a semi‐empirical GSL model. Here we find median projections of 58 and 68 cm for 1.5°C and 2°C temperature pathways. The 90% uncertainty ranges are 67 and 82 cm respectively. Regional projections show similar patterns for both temperature pathways, though differences vary between the median projections (2–10 cm) and 95th percentile (5–20 cm) for the bulk of oceans using process‐based approach and 10–15 cm (median) and 15–25 cm (95th percentile) using the semi‐empirical approach. Plain Language Summary: The sea level you experience at the coast can be estimated by the sum of contributions from ocean expansion, currents, ice melt from glaciers and ice sheets, land‐water extraction/damming, and land motion. How sea level changes depends strongly on where you are because each contribution has a unique pattern. We use knowledge of these changes to make projections about future sea‐level rise. We estimate how much sea‐level could change if societies achieve either of the Paris Climate Agreement's temperature targets by 2100. If we reach 1.5°C or 2.0°C by 2100, GSL should rise around 44–50 cm, respectively. Using a slightly different method we find the global rise could be 58–68 cm. An incomplete picture of the sea‐level components means that estimates could be out by up to 80 cm, though all projections show a sea‐level rise of at least 20 cm. Key Points: We use a novel method to make sea‐level projections for global temperature pathways Median global sea‐level projections for 1.5 and 2 degrees C in 2100 are 44 cm and 50 cm respectively Using a semi‐empirical method, median global projections for 1.5 and 2 degrees C in 2100 rise to 58 cm and 68 cm